Gelatin Promotes Cell Retention Within Decellularized Heart Extracellular Matrix Vasculature and Parenchyma - Tang-Quan, Karis R. (Cell Mol Bioeng, 2020)
INTRODUCTION: Recellularization of organ decellularized extracellular matrix (dECM) offers a potential solution for organ shortage in allograft transplantation. Cell retention rates have ranged from 10 to 54% in varying approaches for reseeding cells in whole organ dECM scaffolds. We aimed to improve recellularization by using soluble gelatin as a cell carrier to deliver endothelial cells to the coronary vasculature and cardiomyocytes to the parenchyma in a whole decellularized rat heart. METHODS: Rat aortic endothelial cells (RAECs) were perfused over decellularized porcine aorta in low (1%) and high (5%) concentrations of gelatin to assess attachment to a vascular dECM model. After establishing cell viability and proliferation in 1% gelatin, we used 1% gelatin as a carrier to deliver RAECs and neonatal rat cardiomyocytes (NRCMs) to decellularized adult rat hearts. Immediate cell retention in the matrix was quantified, and recellularized hearts were evaluated for visible contractions up to 35 days after recellularization. RESULTS: We demonstrated that gelatin increased RAEC attachment to decellularized porcine aorta; blocking integrin receptors reversed this effect. In the whole rat heart gelatin (1%) increased retention of both RAECs and NRCMs respectively, compared with the control group (no gelatin). Gelatin was associated with visible contractions of NRCMs within hearts (87% with gelatin vs. 13% control). CONCLUSIONS: Gelatin was an effective cell carrier for increasing cell retention and contraction in dECM. The gelatin-cell-ECM interactions likely mediated by integrin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12195-020-00634-z) contains supplementary material, which is available to authorized users.